Successful treatment with 308‐nm monochromatic excimer light and subsequent tacrolimus 0.03% ointment in refractory plasma cell cheilitis. Issue 6 (27th April 2013) - Yoshimura, Kazuhiro; Nakano, Shunji; Tsuruta, Daisuke; Ohata, Chika; Hashimoto, Takashi
Abstract Plasma cell cheilitis is a chronic inflammatory disease that presents with erythema, erosions, ulcers and occasional nodules within the mucosa, including the lips. It is histopathologically characterized by dense plasma cell infiltration in the lamina propria of the mucous membranes. Several treatments for plasma cell cheilitis have been reported, including topical steroids, topical antibiotics or topical tacrolimus. However, 308‐nm monochromatic excimer light (MEL) has never been reported as a treatment option, while it was reported to be very effective in treating erosive oral lichen planus. We report a 62‐year‐old man who had chronic plasma cell cheilitis on the lower lip, which was refractory to topical and systemic corticosteroid. The lesion and severe pain were significantly improved by the treatment with nine sessions of 308‐nm MEL twice per week with a total dose of 1120 mJ/cm2. However, the lesion gradually worsened after treatment frequency was reduced to once per month. Subsequent tacrolimus 0.03% ointment cleared the lesion completely in a month and no recurrence was observed a year later. Refractory plasma cell cheilitis and concomitant severe pain quickly responded to 308‐nm MEL when administrated twice per week. Because the long interval between each MEL treatment seemed ineffective to improve the lesion, appropriate frequency and adequate total dose of MEL treatment may be necessary for a successful treatment.